Peningkatan Kapasitas Masyarakat dan Identifikasi Potensi Wisata dalam Pengembangan Desa Watu Tiri Sebagai Desa Wisata - Rostini, Ida Ayu; Rudiyanto, Roseven (Sekolah Tinggi Pariwisata AMPTA, 2021)
Community Capacity Building and Identification of Tourism Potential in the Development of Watu Tiri Village as a Tourism Village This community service activity aims to increase the capacity of the Watu Tiri Village community in the tourism sector and identify existing tourism potentials. In this activity, there are three approaches taken, including Participatory Rural Appraisal (PRA), Community-based development, and participatory. Data collection used focus group discussion (FGD) techniques and field observations. The tourism potentials identified in this community service activity include Mberenang Beach and hot springs as natural tourism potential, while cultural potential includes the activity of weaving single for women and traditional ceremonies in Watu Tiri Village. It can be concluded that in developing Watu Tiri Village as a tourism village, assistance activities such as promotion and e-commerce training, guiding training and English language training, and improving the mitigation system in the Mberenang Beach area are still needed to improve its image.